Attack on Louisbourg. : the fleet commanded by the Honble Adml Boscawen, the army by Major Genl Amherst : engrav'd for Mant's History of the war in North America - Kitchin, Thomas, 1718-1784 ([publisher not identified], 1772)
Statement of responsibility: by T. Kitchin, hydrographer to his Majesty. Relief shown by hachures. Oriented with north to the upper right. Shows troop landings, batteries, and fortifications. To face page 109." Mante's History was published in 1772." Scale ca. 1:19,000